Influence of Bimbing Wuluh Flower (Averrhoa Bilimbi L.) Recipation on Healing Cough in Young Children - Mutiara Gunawardani (International Journal Of Health Science, 2025)
Cough in toddlers is a common respiratory complaint and can disrupt sleep, appetite, and well-being. Synthetic therapies sometimes cause side effects, so the use of herbs is becoming an increasingly popular alternative. Starfruit flowers (Averrhoa blimbi L.) are rich in saponins, flavonoids, and tannins, which function as expectorants, antitussives, and anti-inflammatories. This pre-experimental study with a one-group pretest-posttest design aims to evaluate the effectiveness of starfruit flower decoction in relieving cough in toddlers. A total of 15 toddlers aged 1-5 years with mild to moderate cough without other therapies were given starfruit flower decoction (10 flowers boiled in 200ml of water) twice a day, 2 tablespoons per dose for 5 days. The results of the Wilcoxon test showed that the average cough frequency decreased from 8.0 ± 0.6 to 1.8 ± 0.7 (p = 0.002). This finding confirms that the decoction of starfruit flowers is effective in relieving cough in toddlers. It is recommended that this decoction be considered as a safe and easy-to-apply complementary therapy at home.